x = 4y + 3, 2x + y = -3 System of Equations

Question

x = 4y + 3, 2x + y = -3
System of Equations

in progress 0
Dulcie 6 months 2021-08-08T23:38:15+00:00 2 Answers 5 views 0

Answers ( )

    0
    2021-08-08T23:39:44+00:00

    Answer:

    x = -1, y = -1

    Step-by-step explanation:

    x = 4y + 3

    2x + y = -3

    We have the value of x in terms of y, so we substitute that in 2x + y = -3:

    2(4y+3)+y = -3

    8y+6+y = -3

    9y = -9

    y = -1

    Now we substitute the value of y in x = 4y + 3:

    x = 4(-1)+3

    x = -1

    0
    2021-08-08T23:39:50+00:00

    Answer:

    y = -1 & x = -1

    Step-by-step explanation:

    x = 4y + 3 …. ( 1)

    2x + y = -3 ……..(2)

    substitute the 4y + 3 as x in the second equation

    2( 4y + 3) + y = -3

    simplify and solve for y

    8y + 24 + y = -3

    9 y + 24 = -3

    9y = -3 -24

    9y = -27

    y = -27 / 9

    y = -1

    Now, substitute the value of y -1 in first equation

    x = 4y + 3

    solve for x

    x = 4 ( – 1 ) + 3

    x = -4 + 3

    x = -1

Leave an answer

Browse

Giải phương trình 1 ẩn: x + 2 - 2(x + 1) = -x . Hỏi x = ? ( )